Autoimmune encephalitis - Davydovskaya, M V; Boyko, A N; Beliaeva, I A; Martynov, M Yu; Gusev, E I (Zhurnal nevrologii i psikhiatrii imeni S.S. Korsakova, 2015)
The authors consider the issues related to pathogenesis, clinical features, diagnosis and treatment of autoimmune encephalitis. It has been demonstrated that the development of autoimmune encephalitis can be associated with the oncologic process or be of idiopathic character. The pathogenesis of autoimmune encephalitis is caused by the production of antibodies that directly or indirectly (via T-cell mechanism) damage exo-and/or endocellular structures of the nerve cells. The presence of antobodies to endocellular structures of neurons in the cerebrospinal fluid of patients with autoimmune encephalitis in the vast majority of cases (> 95%) indicates the concomitant oncologic process, the presence of antibodies to membranes or neuronal synapses can be not associated with the oncologic process. Along with complex examination, including neuroimaging, EEG, cerebrospinal fluid and antibodies, the diagnostic algorithm in autoimmune encephalitis should include the search for the nidus of cancer. The treatment algorithm in autoimmune encephalitis included the combined immunosupressive therapy, plasmapheresis, immunoglobulines, cytostatics as well as treatment of the oncologic process.